Down‐regulation of dishevelled‐2 inhibits cell proliferation and invasion in hepatoblastoma. Issue 7 (12th March 2018) - Huang, Siqi; Chen, Jing; Tian, Ruicheng; Wang, Jing; Xie, Chenjie; Gao, Hongxiang; Shan, Yuhua; Hong, Jie; Zhang, Zhen; Xu, Min; Gu, Song
Abstract: Background: Hepatoblastoma (HB) is the most common liver cancer found in early childhood. These patients suffer poor outcomes and need novel therapies. An abnormal activation of Wnt signaling is the hallmark of HB tumorigenesis, and its pathway is a potential candidate for a pharmacological intervention. Procedure: Tissue samples of patients with HB were collected for RNA‐seq, quantitative real‐time PCR, and immunohistochemistry to identify if disheveled‐2 (Dvl‐2) was a target gene. The correlation between Dvl‐2 expression and different clinicopathological features was analyzed using statistical methods. Proliferation and invasion assays were applied after knocking down Dvl‐2 by shRNA in HepG2 and Huh6 HB cell lines. The antitumor effect of niclosamide on HB was ascertained in vitro and in vivo. Results: Dvl‐2 was overexpressed in 90% of patients with HB, and Dvl‐2 expression was positively correlated with the age of patients with HB. Knockdown of Dvl‐2 could inhibit proliferation and invasion of HB cell lines. Also, niclosamide, a Food and Drug Administration approved antihelminth compound, could effectively inhibit HB cell growth in vitro and in vivo via downregulation of Dvl‐2 and β‐catenin expression. Conclusions: Our results implicate that Dvl‐2 is a potential therapeutic target in HB, and niclosamide could have clinical potential to treat patients with HB.